Pengaruh Harga dan Citra Merek Terhadap Keputusan Pembelian Produk dari CV. Tri Utami Jaya di Kota Mataram - Ayunda, Nur; Retnowati, Weni (Postgraduate, University of Mataram, 2025)
This study aims to find out and explain the influence of price and brand image on product purchase decisions from CV. Tri Utami Jaya in Mataram City. This type of research uses associative quantitative and data collection methods using a survey sample with a sample of 100 respondents. The analysis method in this study uses multiple linear regression analysis using the Stastical Package For The Social Sciences (SPSS) tool. The results of the study showed that price had a positive and significant effect on purchase decisions with a calculated t-value of 3,459>1,984. And Brand Image has a positive and significant effect on product purchase decisions from CV. Tri Utami Jaya in Mataram City with a calculated t value of 6,878>1,984. The results of this research can be used as a basis for improving purchasing decisions by developing the benefits of price and brand image.